Benefits and Limitations to Plastic Mulching and Nitrogen Fertilization on Grain Yield and Sulfur Nutrition: Multi-Site Field Trials in the Semiarid Area of China - Luo, Laichao; Hui, Xiaoli; He, Gang; Wang, Sen; Wang, Zhaohui; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
Plastic mulching (PM) is widely used to improve crop water use efficiency and grain yield, but few studies have reported the effects of PM on cereal crop quality, especially sulfur (S) nutrition of wheat, which has significant effects on grain protein content, dough rheology, baking quality and human health. To fill this knowledge gap, we conducted a multi-site field experiment on the Loess Plateau from 2014–2016 to study the effects of PM combined with nitrogen (N) fertilizer on grain yield, shoot S accumulation, and grain S concentration of winter wheat in dryland. Compared with no mulching (NM), PM increased grain yield by 13.7% but decreased grain S concentration, S requirement for 1000 kg–1 grain, soil available S concentration, and post-anthesis S uptake by 9.0%, 9.7%, 24.4%, and 51.8%, respectively. Plastic mulching significantly increased shoot S accumulation at anthesis by 19.2%, but there was no significant difference at maturity. Additionally, grain S concentration and S requirement had a linear-plateau relationship with N fertilization amount, reaching maximum values at 110 and 127 kg N ha–1 under PM, 37.5% and 27.0% higher than those under NM. Furthermore, shoot S accumulation and N application rates well-fitted the linear-plateau model at anthesis and maturity. At maturity, straw, grain, and shoots accumulated the most S at threshold N rates of 120, 85 and 110 kg N ha–1, respectively. Crucially, stem + leaf S concentration at anthesis had a significant linear relationship with grain S concentration under PM; a 1 g kg–1 increase in stem leaf concentration corresponded with a 0.24 g kg–1 increase in grain S concentration. This study’s findings suggest that combining soil S supplementation with optimal N fertilizer under PM in northwest China and other regions with similar cropping systems increases grain S concentration and improves nutritional and processing qualities.